Clusters of Resonances for a Non-Self Adjoint Multichannel Discrete Schrödinger Operator - Miranda-Rozas, P; Assal-, M (American Institute of Physics, 2025)
We study the distribution of resonances for discrete Hamiltonians of the form H0 + V near the thresholds of the spectrum of H0. Here, the unperturbed operator H0 is a multichannel Laplace type operator on ℓ2(Z; CN )≅ℓ2(Z) ⊗ CN and V is a non-selfadjoint compact perturbation. We compute the exact number of resonances and give a precise description on their location in clusters around some special points in the complex plane. © 2025 Author(s).